Determination of Machinery Vibration in Radial Sliding Bearings with Integrated Liquid Dampers - Aleksandr Kiryukhin (New Approaches in Engineering Research Vol. 11, 2021)
The use of radial bearings with segments on a self-generated hydrostatic suspension has been substantiated in order to satisfy the requirements for precision positioning of axes and efficiency of stabilization of shaft oscillations of power-consuming rotary machines. The methods of turbomachine dynamical analysis based on the modelling of the quasistationary processes in lubricating films that balance the harmonic loads on the rotor by redistributing the lubricant flow parameters in the bearing with integrated liquid dampers have been further developed. The complex approach for improving functional properties of turbomachine bearings on the basis of multicriteria optimization of hydraulic tracts parameters and lubrication system operating modes is presented.